2019
DOI: 10.1007/978-3-030-06179-1_35
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exogenous Gamma-Aminobutyric Acid on Absorption and Regulation of Ion in Wheat Under Salinity Stress

Abstract: Gamma-aminobutyric acid (GABA), a four-carbon non-protein amino acid, is a significant component of the free amino acid pool, there are numerous reports that rapid and large increases in GABA levels occur in plants, in response to a variety of biotic and abiotic stress. Based on its metabolism and putative roles in plants, GABA is considered a natural chemical to increase wheat salt-tolerance. So this study investigated the exogenous GABA on wheat seedling (Triticum aestivum L. cv. Changwu134 and zhouyuan9369)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As previously documented, GABA may help to improve the production and quality of carrots when grown under water-deficit conditions through its role as a bioregulator of various physio-biochemical phenomena (Ramesh et al 2017;Wang et al 2019). The present study was undertaken to investigate the efficacy of exogenous application of GABA on the pattern of root growth, and the levels of photosynthetic pigments and dietary antioxidants in curtailing the damaging effects of drought in carrots.…”
Section: Introductionmentioning
confidence: 89%
“…As previously documented, GABA may help to improve the production and quality of carrots when grown under water-deficit conditions through its role as a bioregulator of various physio-biochemical phenomena (Ramesh et al 2017;Wang et al 2019). The present study was undertaken to investigate the efficacy of exogenous application of GABA on the pattern of root growth, and the levels of photosynthetic pigments and dietary antioxidants in curtailing the damaging effects of drought in carrots.…”
Section: Introductionmentioning
confidence: 89%
“…The present ndings demonstrated that cellular injuries imposed by salinity is mitigated by GABA as shown by lower MDA content and higher MSI percentage. The alleviative impact of GABA under salinity stress has been also reported in rice (Sheteiwy et al 2019), poplar (Ji et al 2018), wheat (Wang et al 2019), and muskmelon (Jin et al 2019).…”
Section: Discussionmentioning
confidence: 66%
“…First, GABA may act mainly as an osmo-protectant in a non-enzymatic manner to cope with the adverse effects of salinity, which decrease need to the antioxidative protection system. On the other hand, it has been hypothesized that GABA induces salt-tolerance through the regulation of ion channels with high selectivity for K + over Na + to keep a modest accumulation of Na + in plant tissues and to keep a high K + / Na + ratio (Wang et al 2019). The lower Na + accumulation in leaves decreases ROS generation and in turn, reduces the activity of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, GABA can alleviate the inhibition caused by salt stress in wheat through ion balance modifications [38] . In the present study, under favourable incubation conditions, exogenous GABA promoted wheat seed germination, and remarkably, it continued to enhance germination even when wheat seeds were subjected to the demanding conditions of both salt stress (50 mM NaCl) and high temperature (35°C).…”
Section: Discussionmentioning
confidence: 99%